2010
DOI: 10.1126/science.1186056
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Offspring Conflict and Coadaptation

Abstract: The evolution of family life has traditionally been studied in parallel by behavioral ecologists and quantitative geneticists. The former focus on parent-offspring conflict and whether parents or offspring control provisioning, whereas the latter concentrate on the coadaptation of parental supply and offspring demand. Here we show how prenatal effects on offspring begging can link the two different approaches. Using theoretical and experimental analyses, we show that when offspring control provisioning, prenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
164
6
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(176 citation statements)
references
References 27 publications
5
164
6
1
Order By: Relevance
“…Under the mother -offspring co-adaptation hypothesis, an interaction between OFM and OGM is predicted to significantly influence the measured traits, with lower values of maternal care and fitness correlates in mismatched than matched combinations [4,24]. Conversely, under the parental antagonism hypothesis, OGM, OGF and/or an interaction between these two factors (indicative of intragenomic epistasis [9,12]) are expected to significantly influence the measured values of maternal care and fitness correlates of mothers and offspring.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Under the mother -offspring co-adaptation hypothesis, an interaction between OFM and OGM is predicted to significantly influence the measured traits, with lower values of maternal care and fitness correlates in mismatched than matched combinations [4,24]. Conversely, under the parental antagonism hypothesis, OGM, OGF and/or an interaction between these two factors (indicative of intragenomic epistasis [9,12]) are expected to significantly influence the measured values of maternal care and fitness correlates of mothers and offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, maternally inherited genes expressed in offspring are predicted to limit the level of offspring demand because females suffer from the costs of exaggerated offspring demand and have siblings that are equally related from their maternal side [9]. While a growing number of experimental and theoretical studies show that parental antagonism and parent-offspring co-adaptation are keystones in the evolution of family life [4,8,9], little is known about their simultaneous effects within families and its consequence on family interactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the similarity of these patterns is somewhat complicated by the unexpected finding that Babesia-treated offspring gained less weight than control offspring during the pre-weaning period. It is conceivable that increased suckling observed among the offspring of dams that had experienced infection was driven by the offspring rather than by the mothers, and hence may have reflected the need to increase suckling time owing to potentially limited or lower quality milk production [75][76][77]. An earlier experiment by Barnard et al [37] showed that suckling behaviour affected both social rank and immunity in mice, with aggressiveness inversely proportional to suckling, but, as in our study, it was not possible to determine whether this was offspring-or parentdriven.…”
Section: Discussionmentioning
confidence: 99%